Natural resources’ impact on capital flow and conflict relationship in Africa: a novel insight from GMM and quantile regression - Snow Sini, Sini; Abdul-Rahim, A.S.; Lee Chin, Chin; Said, Rusmawati; Sulaiman, Chindo (Elsevier, 2022)
This paper investigates the impact of natural resources on conflict-capital flows relationship in 54 African economies over the 2010–2019 period. Applying econometric method of data analysis, the empirical estimation hinges on generalized method of moments, unit root tests, Kao cointegration test, cross-sectional dependence test, and quantile regression. The estimated results revealed the following. First, generalized method of moments revealed that conflict persistently decreases capital flow. Second, unit root test for both first-and-second generation affirmed stationarity. Third, Kao cointegration test revealed long-run relationship among the modelled variables. Fourth, tests for cross-sectional dependency revealed the existence of structural break and cross-sectional dependence of countries. Fifth, the quantile regression indicated that conflict decreases capital flows for all parts of the distribution, even when the initial degree of capital flows is at 25th percentile. Furthermore, the interaction term (i.e., interacting conflict with the natural resource) showed that natural resources are the reason for the inflow of capital into the Africa. In other words, conflict decreases capital flow into Africa when the level of natural resource extraction is low and vice versa. As such, there is a need to develop and implement policies aimed at increasing sources of capital inflow into the Africa’s economy, such as domestic capital productivity, while decreasing all forms of conflict that can impede capital inflow. To avoid over-reliance on natural resources, policies should aim at creating a peaceful and conducive environment for foreign direct investment inflows to service sectors such as education, financial institutions and others. Thus, there is need to combat conflict in the continent.